Health benefits of medicinal plant natural products via microbiota-mediated different gut axes - Xiang Li; Yufan Liu; Ning Liu; Hanning Wu; Kexin Cong; Linnan Duan; Tianli Chen; Jie Zhang (Pharmacological Research)
This review examines the multifaceted roles of medicinal plant natural products in influencing gut microbiota and their subsequent impact on various organ systems through established gut axes, including the gut-brain, gut-liver, gut-heart, gut-lung, and gut-kidney axes. Medicinal plant natural products have exhibited diverse pharmacological activities, including modulation of microbiota composition, enhancement of metabolic processes, and alleviation of inflammation and oxidative stress. Evidence suggests that these components can ameliorate conditions such as neurological disorders, metabolic syndrome, and chronic kidney disease by restoring microbial balance and improving gut barrier integrity. Furthermore, the review highlights the potential of medicinal plant natural products to foster beneficial microbial communities and improve gut health, which may lead to reduced disease severity and inflammation. By comprehensively analyzing current literature, this review provides a foundation for future research aim at exploring the therapeutic applications of medicinal plant natural products in disease prevention and treatment. The findings underscore the need for further studies to elucidate the underlying mechanisms of action and validate the clinical efficacy of medicinal plant natural products in managing chronic conditions through gut microbiota modulation.